A Bibliometric Analysis of Middlemen Research: A Closer Look at Agricultural Marketing - Savelia Salsa Bila; Idqan Fahmi; Suprehatin (Business Review and Case Studies, 2022)
The presence of an aggregator business in agricultural marketing complicates the current understanding of middlemen. The presence of intermediaries has begun to be questioned and even considered a threat to the supply chain. This study aims to (1) analyze the evolution of research middlemen in influencing agricultural marketing and (2) identify what issues are developing in middlemen in agricultural marketing. Data were analyzed from 425 journals registered with Scopus from 1974 to 2021. The data were then processed and analyzed using Tableau, Ms. Excel, and VOSviewer. It generates bibliometric maps against middlemen in agricultural marketing through bibliometric analysis. The development of the middlemen issue discusses its implications for agribusiness management, social capital, value chains, and prices. The existence of middlemen cannot be fully considered as threatening the supply chain. The involvement of middlemen in the supply chain still has a strong influence on farmers, especially in developing countries. Keywords: agricultural marketing, bibliometric analysis, middlemen, supply chain, VOSviewer